Development of VILLA Media to Enhance Fourth-Graders’ Cognitive Outcomes on Hindu-Buddhist Kingdoms - Dean Nurmala Sr; Eka Titi Andaryani (FKIP - Universitas Riau, 2026)
Many fourth-grade students struggle with abstract historical topics in the IPAS subject, leading to low cognitive learning outcomes. This research aims to develop, evaluate the feasibility, and test the effectiveness of VILLA (Video Lagu Anak) media in improving student understanding of Hindu-Buddhist Kingdoms. This study utilized a Research and Development (R&D) design with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, involving 35 students at SDN Tambakaji 01. Data were collected through expert validation sheets, interviews, and pre-test/post-test instruments. The media’s feasibility was evaluated by 3 expert validators, including media, subject matter, and language experts. The results indicate that VILLA media is highly feasible, achieving an average expert validation score of 95% and a student response rate of 95%. Statistical analysis incorporating the Shapiro-Wilk normality test, Wilcoxon Signed-Rank test, and N-gain calculation showed a significant improvement in learning outcomes (p = 0.000). Furthermore, the N-gain score of 0.74 confirms that the media is highly effective. In conclusion, VILLA media is a valid, practical, and effective instructional tool that successfully simplifies complex historical concepts and significantly enhances the cognitive retention of fourth-grade students.